Tax Morale and Compliance : Review of Evidence and Case Studies for Europe - Torgler, Benno (2012)
This paper provides an overview of the literature on tax morale and tax compliance. Most of the material here is based on research that I have conducted together with my co-authors over the last 10 years. Europe has a dominant place in this paper. Sometimes results derived from other countries are discussed that could be relevant for Europe. The overall findings show the importance of accountability, democratic governance, efficient, and transparent legal structures and therefore trust within the society to enforce tax compliance and tax morale.